Islamic Educational Leadership Trends: Interlinking Leadership, Human Development, and Sustainability - Abdulrohim E-sor; Md. Ishaque (Walidem Institute and Publishing (WIP), 2025)
Objective: This research aims to explore emerging trends and key themes in the Islamic Educational Leadership literature, with a focus on their relationship to human development and sustainability. The study also seeks to identify influential topics and emerging keywords, thereby filling the gap in data-driven integrated analysis in these areas. Theoretical framework: Combines Islamic Educational Leadership Theory, Organizational Change Theory, and Sustainable Development principles, with the support of transformational, distributed leadership theory, and Human Capital Theory to link educational practices, individual development, and socio-economic-environmental well-being. Literature review: Transformational and distributed leadership play a role in curriculum innovation, HR quality improvement, and sustainable practices. Comprehensive bibliometric studies that map keywords, authors, and clusters are still rarely conducted. Method: This study uses a quantitative approach through bibliometric analysis and network analysis of 596 academic documents obtained from the Scopus database (period 2020–2025). Bibliometric analysis is used to evaluate publication patterns, citation rates, and influential authors, while network analysis maps the relationships between keywords, author collaboration, and the formation of research clusters. Results: The results of the analysis show the existence of a collaborative and cross-disciplinary research environment, with three main thematic clusters: (1) curriculum design and innovation, (2) leadership and human development, and (3) sustainability in higher education. In addition, new keywords were found that represented emerging research trends. Implications: Provide strategic guidance for practitioners and policymakers in professional development, the application of sustainable practices, and future research directions. Novelty: A recent analysis (2020–2025) that integrates education leadership, human development, and sustainability uncovers new trends and linkages that have not been documented.